Evaluation of commercial enzyme supplementation on growing pig performance - J Y Jacela; P Brown; Michael D Tokach; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 1,129 pigs were used in a 56-d study to evaluate the effect of a commercial enzyme on growth performance and assess its energy replacement value in swine diets. Pigs were blocked on the basis of pen weights and allotted to 1 of 6 dietary treatments fed in 3 phases. Dietary treatments had increasing levels of fat (0, 2.5, and 5.0%) with or without added enzyme (0.05% or 0% Agri-King REAP). Phase 1 was fed from approximately 75 to 110 lb BW, phase 2 was fed from 110 to 160 lb BW, and phase 3 was fed from 160 to 200 lb BW. Diets were based on cornmeal and soybean meal with 15% added dried distillers grains with solubles (DDGS) and balanced to a constant lysine to calorie ratio (2.98, 2.68, and 2.38 g/Mcal ME for phases 1, 2, and 3, respectively) within diet phase. Pen weights and feed intake were obtained every 2 wk from d 0 to 56 to determine ADG, ADFI, and F/G. There were no interactions (P>0.11) between the addition of enzyme and added fat for ADG, ADFI, or F/G of pigs throughout the duration of the 84-d experiment. There was no difference (P = 0.53) in ADG, ADFI, or F/G between pigs fed diets with and without added enzyme. However, pigs fed diets with increasing added fat levels had improved (linear, P<0.03) ADG and F/G. In conclusion, the addition of the commercial enzyme did not affect growth performance of pigs in this study, but ADG and F/G improved with the addition of fat in the corn-soybean meal-based diets with 15% DDGS.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Enzyme; Fat; Growth; Pig